2022
DOI: 10.3389/fgwh.2022.932997
|View full text |Cite
|
Sign up to set email alerts
|

Unmet need for contraception and its associated factors among adolescent and young women in Guinea: A multilevel analysis of the 2018 Demographic and Health Surveys

Abstract: Despite the recent repositioning efforts to increase the use of modern contraceptives, the prevalence of unmet need for contraception remains high among adolescent and young women in Guinea. This study analyzed the individual and contextual factors associated with the unmet need for contraception among adolescent and young women in 2018 in Guinea. We conducted a secondary analysis of the 2018 Demographic and Health Survey data. Multilevel mixed-effects logistic regression models were used to assess the associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…The association between age and the unmet need for contraception is complex and depends on the demographic and societal context. For example, a study conducted among Guineans found a higher prevalence of unmet need for contraceptives among adolescents compared to young women as young women are more likely to live in union and may desire to have children while adolescents may face stigma of using contraceptive services outside their marriage [ 32 ]. Recognizing and addressing the unique needs of these age groups can enhance the effectiveness of reproductive health policies and better support individual’s needs.…”
Section: Discussionmentioning
confidence: 99%
“…The association between age and the unmet need for contraception is complex and depends on the demographic and societal context. For example, a study conducted among Guineans found a higher prevalence of unmet need for contraceptives among adolescents compared to young women as young women are more likely to live in union and may desire to have children while adolescents may face stigma of using contraceptive services outside their marriage [ 32 ]. Recognizing and addressing the unique needs of these age groups can enhance the effectiveness of reproductive health policies and better support individual’s needs.…”
Section: Discussionmentioning
confidence: 99%
“…6 A study conducted in Guinea in 2022 reported a prevalence of unmet need for contraception of 22.6%. 7 Women's decision-making power regarding the use of family planning services is a real problem in Guinea. Yet there are no studies examining the factors associated with this decision-making power among married women in the country, where the cost-free provision of family planning methods is not fully in place.…”
Section: Introductionmentioning
confidence: 99%